A Straightforward Approach of Wet‐Spinning Poly(3,4‐ethylenedioxythiophene):Polystyrene Sulfate Fibers for Use in All Conducting Polymer‐Based Textile Actuators - Mathis Bruns; Shayan Mehraeen; Jose G. Martinez; Johannes Mersch; Iris Kruppke; Edwin W. H. Jager; Chokri Cherif (Advanced Intelligent Systems)
Poly(3,4‐ethylenedioxythiophene) (PEDOT), an inherently electrically conductive or conjugated polymer (CP), exhibits the potential to play a significant role in the development of innovative fiber materials for use in smart textiles, such as wearables. Furthermore, these fibers can function as artificial muscles in the emerging field of interactive fiber rubber composites. This study introduces a straightforward and efficient method for creating PEDOT‐based, biomimetic, fiber‐shaped, linearly contracting ionic electroactive polymer actuators. To achieve this, a wet‐spinning technique is presented, which enables a continuous production of PEDOT:polystyrene sulfate (PSS) fibers at high production rates of 34 m h−1, an additional fiber washing step and a sulfuric acid posttreatment step to increase the fibers conductivity. The fibers provide a high conductivity of 1028 S cm−1, maximum tensile strength reaching 182 MPa, and a maximum elongation of 24%. When utilized as CP actuators in an aqueous sodium dodecylbenzenesulfonate electrolyte medium, the fibers demonstrate a repeatable maximum isometric contractile force of 1.64 mN and repeatable linear contractile strain up to 0.56%. Furthermore, a high level of cyclic long‐term actuation stability can be demonstrated. Notably, these contractile strains are, to the best of knowledge, the highest reported values for pristine PEDOT:PSS fibers.